ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG TERIGU MENGGUNAKAN METODE EOQ PADA PABRIK MIE MUSBAR PEKANBARU - Rakian, Atdri; Hamid, Liswar; Daulay, Iwan Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the optimal amount of the purchase of raw materials, amount of safety stock, reorder point, and the total inventory cost for the year 2009-2013 in Pabrik Mie Musbar Pekanbaru. The basic method applied in this research is descriptive analysis. Research location named Pabrik Mie Musbar PekanbaruLocation of the study determined intentionally (purposive) at Pabrik Mie Musbar considering that Pabrik Mie Musbar is a factory producing noodles are made from wheat flour, which Pabrik Mie Musbar should be able to determine how much flour are ordered so that the cost of capital is not exhausted in the purchase of flour wheat alone. The use of the method Economic Order Quantity can determine the optimal quantity and frequency of ordering raw materials flour so that the inventory cost can be more efficient.Based on the calculations, that the purchase of raw materials wheat flour according to the EOQ method for years 2009-2013 is greater than the policy of the company and the quantity of flour purchase an average of the years 2009-2013 amounted to 987,3956 sack. Safety stock average for the period 2009-2013 amounted to 69,067 sacks. During the years 2009-2013 Pabrik Mie Musbar not apply any reorder point, while the average of reorder point according to the EOQ method of 94,06668 sack. The total cost of raw material inventories during the year 2009-2013 according to the EOQ method is smaller than the policy of the company and the total cost of inventory on average in 2009-2013 amounted to Rp 410.948,3272. From the research that has been done shows that the inventory control flour in Pabrik Mie Musbar during years 2009-2013 is inefficient.Keywords: Purchasing, Safety Stock, Reorder Point and Total Inventor Cost